Antimicrobial, cytotoxicity, anticancer and antioxidant activities of Jatropha zeyheri Sond. roots (Euphorbiaceae) - N I Mongalo; O S Soyingbe; T J Makhafola (Asian Pacific Journal of Tropical Biomedicine, 2019)
Objective: To evaluate the antimicrobial, antioxidant, cytotoxicity and anticancer activity of fractions from Jatropha zeyheri roots and to explore the phytochemical profile of the most biologically active fraction. Methods: Fractions from Jatropha zeyheri ethyl acetate extract were investigated for antimicrobial activity against a plethora of pathogenic microorganisms of different origins. The cytotoxicity studies of fractions were evaluated in vitro using tetrazolium-based calorimetric assay against human dermal fibroblast, colon adenocarcinoma (Caco-2), breast cancer (MCF-7) and lung cancer (A547) cell lines. The anti-oxidant activity of fractions was determined in vitro against 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azino-bis-(3-ethylbenzothiazoline- 6-sulfonic acid) diammonium salt (ABTS) and chelation of iron (Fe2+). Gas chromatography mass spectrometry analysis was performed to detect phytochemical constituents in fraction with potent biological activity. Results: Fraction 2 of Jatropha zeyheri roots exhibited the lowest minimum inhibitory concentration of 40 μg/mL against Klebsiella pneumoniae and 80 μg/mL against Candida albicans, Staphylococcus aureus and Mycoplasma hominis. The fractions revealed some varying degrees of cytotoxicity against human dermal fibroblasts yielding LC50 values ranging from 28.96 to 166.52 μg/mL. Fraction 3 exhibited the highest selectivity index value of 2.08 against Klebsiella pneumoniae. Moreover, fraction 2 selectively inhibited the growth of Caco-2 with LC50 of 8.83 μg/mL, compared to other cancerous cell lines. Fraction 2 of Jatropha zeyheri further exhibited IC50 of 19.66, 22.63 and 1.82 μg/mL against DPPH, ABTS and Fe2+, respectively. Gas chromatography mass spectrometry analysis revealed the presence of cyclotetracosane (10.08%), 9-hexacosene (9.40%), hexadecanoic acid (3.90%), (Z)-9-octadecenamide (3.63%), octacosane (2.27%), 11-n-decylheneicosane (2.23%), ethyl vallesiachotamate (2.17%), heneicosanoic acid (2.10%), and octadecanoic acid (2.08%) in fraction 2 of ...